The effects of upper- vs. lower-body aerobic exercise on perceived pain in individuals with chronic knee pain: a randomised crossover trial - Rachel Deere; Rachel Deere; Rachel Deere; Rachel Deere; Enhad Chowdhury; Enhad Chowdhury; Enhad Chowdhury; Abby Tabor; Dylan Thompson; Dylan Thompson; James L. J. Bilzon; James L. J. Bilzon; et al. (Frontiers in Pain Research, 2023)
Background and objectivesSome patients with chronic knee pain experience an increase in knee pain following a single bout of exercise involving their knee joint, which can negatively affect exercise adherence and thus result in reduced overall health and lack of disease management. We want to determine whether a single bout of upper-body (UB) aerobic arm-ergometry exercise is effective in reducing the experience of pain in those with chronic knee pain compared with lower-body (LB) aerobic leg ergometry exercise.MethodsA total of 19 individuals (women = 11, men = 8; age = 63 ± 8 years; body mass index = 24 ± 3 kg/m2) who suffered from chronic knee pain for ≥3 months took part in this study. Arm-ergometry and cycle-ergometry exercises were performed for 30 min at a moderate intensity, separated by 7 days. Pain intensity was assessed by means of a visual analogue scale (VAS) pre- and post-exercise and for 7 days post-exercise. Pressure pain threshold (PPT) and mechanical detection threshold (MDT) were measured pre- and post-exercise at both local and distal anatomical sites. Data are presented as mean ± SD.ResultsVAS pain was significantly reduced (p = 0.035) at 1 day post-exercise following the UB exercise trial (−1.4 ± 0.8) when compared with the LB exercise trial (+0.1 ± 2.1). Both UB and LB exercises were effective in reducing local and distal PPT. MDT responses were heterogeneous, and no differences between the UB and LB exercise conditions were noted.ConclusionAn acute bout of upper-body aerobic arm-ergometry exercise evoked a significant decrease in the affected knee joint pain in individuals with chronic knee pain of up to 24 h/1 day post-exercise compared with lower-body aerobic exercise. While the exact mechanisms remain unclear, upper-body exercise may offer a viable, novel therapeutic treatment for patients with chronic knee pain.